Genetic diversity and population structure of Theileria parva in South Sudan - Salih, Diaeldin A.; Mwacharo, Joram M.; Pelle, Roger; Njahira, Moses N.; Odongo, David O.; Mbole-Kariuki, Mary N.; Marcellino, Wani L.; Malak, Agol K.; Kiara, Henry K.; El Hussein, A.R.M.; Bishop, Richard P.; Skilton, Robert A. (Elsevier, 2018)
Theileria parva is a parasitic protozoan that causes East Coast fever (ECF), an economically important disease of cattle in eastern, central and southern Africa. In South Sudan, ECF is considered a major constraint for livestock development in regions where the disease is endemic. To obtain insights into the dynamics of T. parva in South Sudan, population genetic analysis was performed. Out of the 751 samples included in this study, 178 blood samples were positive for T. parva by species-specific PCR, were collected from cattle from four regions in South Sudan (Bor = 62; Juba = 45; Kajo keji = 41 and Yei = 30) were genotyped using 14 microsatellite markers spanning the four chromosomes. The T. parva Muguga strain was included in the study as a reference. Linkage disequilibrium was evident when populations from the four regions were treated as a single entity, but, when populations were analyzed separately, linkage disequilibrium was observed in Bor, Juba and Kajo keji. Juba region had a higher multiplicity of infection than the other three regions. Principal components analysis revealed a degree of sub-structure between isolates from each region, suggesting that populations are partially distinct, with genetic exchange and gene flow being limited between parasites in the four geographically separated populations studied. Panmixia was observed within individual populations. Overall T. parva population genetic analyses of four populations in South Sudan exhibited a low level of genetic exchange between the populations, but a high level of genetic diversity within each population.